Detection of Thrombosis in the Extracorporeal Membrane Oxygenation Circuit by Infrasound: Proof of Concept - Fuchs, Gabriel (Artif Organs, 2016)
As of today, there exist no reliable, objective methods for early detection of thrombi in the extracorporeal membrane oxygenators (ECMO) system. Within the ECMO system, thrombi are not always fixed to a certain component or location in the circuit. Thus, clot fragments of different shapes and consistencies may circulate and give rise to vibrations and sound generation. By bedside sound measurements and additional laboratory experiments (although not detailed herein), we found that the presence of particles (clots or aggregates and fragments of clots) can be detected by analyzing the strength of infra‐sound (< 20 Hz) modes of the spectrum near the inlet and outlet of the centrifugal pump in the ECMO circuit. For the few patients that were considered in this study, no clear false positive or negative examples were found when comparing the spectral approach with clinical observations. A laboratory setup provided insight to the flow in and out of the pump, confirming that in the presence of particles a low‐amplitude low‐frequency signal is strongly amplified, enabling the identification of a clot.